Drug-eluting beads transarterial chemoembolization by CalliSpheres is effective and well tolerated in treating intrahepatic cholangiocarcinoma patients: A preliminary result from CTILC study. Issue 12 (March 2020) - Luo, Jun; Zheng, Jiaping; Shi, Changsheng; Fang, Jian; Peng, Zhiyi; Huang, Jing; Sun, Junhui; Zhou, Guanhui; Li, Tiefeng; Zhu, Dedong; Xu, Huanhai; Hou, Qinming; et al.
Abstract : Abstract: This study aimed to investigate the efficacy and safety of drug-eluting beads (DEB) transarterial chemoembolization (TACE) treatment in Chinese intrahepatic cholangiocarcinoma (ICC) patients. 37 ICC patients underwent DEB-TACE treatment in CTILC study (registered on clinicaltrials.gov with registry No. NCT03317483) were included in this present study. Treatment response was assessed according to modified Response Evaluation Criteria in Solid Tumors (mRECIST). Overall survival (OS) was calculated from the time of DEB-TACE operation until the date of death from any causes. Liver function change and adverse events (AEs) were recorded during and after DEB-TACE operation. 3 (8.1%) patients achieved complete response (CR) and 22 (59.5%) patients achieved partial response (PR), with objective response rate (ORR) of 67.6%. After DEB-TACE treatment, mean OS was 376 days (95%CI: 341–412 days). Multivariate logistic regression analysis revealed that Bilobar disease ( P = .040, OR: 0.105, 95% CI: 0.012–0.898) and portal vein invasion ( P = .038, OR: 0.104, 95% CI: 0.012–0.881) could independently predict less possibility of ORR. Patients with ALB abnormal, TP abnormal, ALT abnormal and AST abnormal were increased at 1-week post DEB-TACE treatment ( P = .034, P = .001, P < .001, P = .006, respectively), while returned to the levels at baseline after 1 to 3 months (all P > .050). Besides, most of the AEs were mild including pain, fever, vomiting, and nausea in this study. DEB-TACE was effective and well tolerated in treating ICC patients, and bilobar disease as well as portal vein invasion were independently correlated with less probability of ORR achievement.